2008
DOI: 10.1515/znb-2008-1013
|View full text |Cite
|
Sign up to set email alerts
|

Cotonoates A and B, New Aromatic Esters from Cotoneaster racemiflora

Abstract: Phytochemical investigation of the chloroform soluble fraction of the methanolic extract of Cotoneaster racemiflora resulted in the isolation of two new aromatic esters named cotonoates A (1) and B (2) along with the known compound methyl 3,4-dihydroxy-5-methoxybenzoate (3). The structures of the new compounds have been assigned on the basis of spectral analysis including 1D and 2D NMR techniques. Compound 3 shows significant antioxidant and lipoxygenase inhibitory activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…Plants belonging this genus commonly called as "Dağ muşmulası or Tavşan elması" in the different region of Anatolia. In addition, the Cotoneaster species are widely used as culinary plants in different countries including Turkey (Baytop, 1999;Cakilcioglu and Turkoglu, 2010;Khan et al, 2008). Previously, some bioactive compounds were reported in the genus (El-Mousallamy et al, 2000;Khan et al, 2008;Sokkar et al, 2013;Zengin et al, 2014) but so far, there is no information about biological activities and chemical fingerprint of C. integerrimus.…”
Section: Introductionmentioning
confidence: 99%
“…Plants belonging this genus commonly called as "Dağ muşmulası or Tavşan elması" in the different region of Anatolia. In addition, the Cotoneaster species are widely used as culinary plants in different countries including Turkey (Baytop, 1999;Cakilcioglu and Turkoglu, 2010;Khan et al, 2008). Previously, some bioactive compounds were reported in the genus (El-Mousallamy et al, 2000;Khan et al, 2008;Sokkar et al, 2013;Zengin et al, 2014) but so far, there is no information about biological activities and chemical fingerprint of C. integerrimus.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in a set of identified phenolic acids, chlorogenic ( 28 ) and ferulic ( 29 ) acids were noted as the most abundant phenolics in the twigs and fruits of C. integerrimus [ 24 ], the leaves of C. meyeri [ 23 ], the leafy twigs of C. nummularia [ 7 ], and the leafy twigs of C. horizontalis [ 26 ]. Apart from typical phenolic acids, lesser-known compounds, including esters of benzoic and terephthalic acids, named cotonoates A ( 43 ), B ( 44 ), and horizontoates A ( 45 ), B ( 46 ), were isolated from the leafy twigs of C. racemiflora and C. horizontalis , respectively [ 27 , 28 ].…”
Section: Phytochemical Composition Of the Genus Cotoneasmentioning
confidence: 99%
“…Cotoneaster species, as the most widespread plants in East Asia, are also natural medicines with a long traditional use in Iran, Pakistan, Turkey, Mongolia, and Tibet [ 5 , 27 , 45 , 46 ]. Numerous species are known to the local community for their diuretic, astringent, expectorant, hepatoprotective, digestive, cardiotonic, antiviral, and spasmolytic properties.…”
Section: Biological Activities Of the Genus Cotoneaster mentioning
confidence: 99%
“…Racemiside, scopoletin, 7,8-dimethoxy-6-hydroxycoumarin, 3,3',4'-tri-O-methylellagic acid, and cereotagloperoxide isolated from the ethyl acetate-soluble fraction of Cotoneaster racemiflora, showed profound antioxidative activities in the DPPH assay [129].Free radical scavenging activity measured by 1,1diphenyl-2-picryl-hydrazil (DPPH) showed that methyl 3,4-dihydroxy-5-methoxybenzoate isolated from the plant possessed significant antioxidant (IC 50: 9.7±0.12µm). The spectrophotometric method showed that the same compound exerted lipoxygenase inhibitory activities (IC 50: 19.5±0.07 µm) [130].Antioxidant capacities of ethyl acetate, methanol and water extracts of the plant were evaluated by free radical scavenging assay (DPPH, ABTS and O 2 ), reducing power, phosphomolybdenum, β-carotene/linoleic acid bleaching and metal chelating assays. The highest DPPH and O 2 scavenging activities were exerted by water extract of the plant, followed by the methanol extract.…”
Section: Cotoneaster Racemifloramentioning
confidence: 99%